2007
DOI: 10.1063/1.2435348
|View full text |Cite
|
Sign up to set email alerts
|

Efficient coupling of high intensity short laser pulses into snow clusters

Abstract: Measurements of energy absorption of high intensity laser pulses in snow clusters are reported. Targets consisting of sapphire coated with snow nanoparticles were found to absorb more than 95% of the incident light compared to 50% absorption in flat sapphire targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…There is a substantial body of experimental work on the effect of surface roughness of targets on laser-plasma coupling, including the laser absorption and the production efficiency and energy spectrum of the generated xrays or ions [14][15][16][17][18][19][20][21]. Various simulation works attribute the observed improvement to a surface area increase and the local field enhancement introduced by the roughness [22][23][24][25].…”
Section: B Target Designmentioning
confidence: 99%
“…There is a substantial body of experimental work on the effect of surface roughness of targets on laser-plasma coupling, including the laser absorption and the production efficiency and energy spectrum of the generated xrays or ions [14][15][16][17][18][19][20][21]. Various simulation works attribute the observed improvement to a surface area increase and the local field enhancement introduced by the roughness [22][23][24][25].…”
Section: B Target Designmentioning
confidence: 99%
“…These targets were engineered by depositing snow on sapphire substrates. It was shown that pre-formed plasma formed by a prepulse may be beneficial to the acceleration process [17,18]. Our experimental results [16] show that the energy of the accelerated protons scales with the power of the laser according to ~ / , like other schemes [19] (see Figure 1).…”
Section: Introductionmentioning
confidence: 52%
“…The subwavelength-multiholes transpiercing the planar target enhance the laser-proton energy conversion efficiency [21][22][23]. The subwavelength microstructured targets [21][22][23][24][25] are propitious to enhance the laser energy absorption. In this paper a e-mail: kwt@cc.utsunomiya-u.ac.jp This is an Open Access article distributed under the terms of the Creative Commons Attribution License 2.0, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%